2010
DOI: 10.1111/j.1742-7843.2009.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Induces Apoptosis in Ovarian Carcinoma Cell Line OVCAR‐3 Through Reactive Oxygen Species‐Dependent Activation of Nuclear Factor‐κB

Abstract: The apoptotic effect of fluoxetine (FLX), an antidepressant, against human epithelial ovarian cancer cell lines OVCAR-3 and SK-OV-3 was investigated in relation to the mitochondria-mediated cell death process and nuclear factor (NF)-jB activation. FLX-induced mitochondrial membrane permeability change and formation of reactive oxygen species, leading to cell death. FLX-induced increase in mitochondrial Bax levels, decrease in cytosolic Bid and Bcl-2 levels, loss of the mitochondrial transmembrane potential, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…We have demonstrated that the anti-angiogenic potential of FLX could be related to its control over the differentiation and further transition of endothelial cells through different angiogenesisrelated stem cell markers in colon preneoplastic lesions ated state, which reduces mitochondrial respiratory rate and energy generation [84][85][86] . FLX was also found to induce ROS generation in human ovarian cancer cell lines, which induced apoptosis through mitochondrial bcl-2-associated X protein, cytochrome c release, caspase-3 activation and p53 expression levels, whilst this treatment further reduced ΔΨm, BH3 interacting-domain death agonist and bcl-2 levels [54] . Similar findings were reported in human neuroblastomas [55] .…”
Section: Flx Reduces Preneoplastic Lesions Acting On Colonic Microenvmentioning
confidence: 95%
See 2 more Smart Citations
“…We have demonstrated that the anti-angiogenic potential of FLX could be related to its control over the differentiation and further transition of endothelial cells through different angiogenesisrelated stem cell markers in colon preneoplastic lesions ated state, which reduces mitochondrial respiratory rate and energy generation [84][85][86] . FLX was also found to induce ROS generation in human ovarian cancer cell lines, which induced apoptosis through mitochondrial bcl-2-associated X protein, cytochrome c release, caspase-3 activation and p53 expression levels, whilst this treatment further reduced ΔΨm, BH3 interacting-domain death agonist and bcl-2 levels [54] . Similar findings were reported in human neuroblastomas [55] .…”
Section: Flx Reduces Preneoplastic Lesions Acting On Colonic Microenvmentioning
confidence: 95%
“…In these epithelial cells, it induces an increase in serotonin (5-HT) levels by blocking L-monoamine oxidase and serotonin reuptake transporters [41][42][43] . On the other hand, FLX has been shown to interfere with the OS machinery in experimental models and humans [44][45][46][47][48][49][50][51][52][53][54][55] . Treatment with FLX was found to reduce malondialdehyde (MDA) and carbonyl levels in stressed rats, whilst it enhanced superoxide dismutase (SOD), catalase, glutathione S-transferase, glutathione reductase and glutathione contents [45,46] .…”
Section: Antidepressant Flx Modulates Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in endogenous norepinephrine have been shown to induce gonadotropin secretion as well [54,60]. Fluoxetine, a type of SSRI, was demonstrated to induce apoptosis of ovarian carcinoma OVCAR-3 cells [61]. Additionally, other studies have shown that sertraline and paroxetine can inhibit HT29 cells and induce alterations in…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine also exerts its anticarcinogenic effects by modulating the permeability of mitochondrial membranes [4]. As a result, there is increased expression of p53 and a decline in intracellular bcl-2 level along with simultaneous augmentation of levels of Bax.…”
mentioning
confidence: 99%